On Epistemic Appropriation - Davis, Emmalon (Ethics, 2018)
In this article, I offer an account of an unjust epistemic practice―namely, epistemic appropriation―that harms marginalized knowers through the course of conceptual dissemination and intercommunal uptake. The harm of epistemic appropriation is twofold. First, while epistemic resources developed within the margins gain uptake with dominant audiences, those resources are overtly detached from the marginalized knowers responsible for their production. Second, epistemic resources developed within, but detached from, the margins are utilized in dominant discourses in ways that disproportionately benefit the powerful.
Keywords: approches et analyses; appropriation épistémique; cours; cycles supérieurs; discipline; discours dominant; droits des personnes; fem9000; injustices épistémiques; inégalités; philosophie; privilèges; rapports de pouvoir; savoirs des marges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Lutter contre les violences conjugales : féminisme, travail social, politique publique - Herman, Elisa; Lagrave, Rose-Marie (Le sens social, 2018)
Comprendre les violences faites aux femmes dans le couple c'est aussi analyser les luttes, les politiques publiques et les actions concrètes déployées en France aujourd'hui. Ce livre prend appui sur une enquête ethnographique menée auprès d'associations spécialisées (souvent membres de la Fédération nationale solidarité femmes), de femmes victimes, de professionnels de nombreuses institutions concernées (justice, police, travail social...) et de personnalités politiques et universitaires actifs sur ces sujets. S'adressant aux universitaires ainsi qu'aux professionnels, l'ouvrage décrit la construction de la cause des violences conjugales, ainsi que les politiques publiques mises en œuvre, dans une démarche sociohistorique. Il met ainsi en lumière la porosité des espaces militant, universitaire et institutionnel. L'analyse des carrières militantes et professionnelles, la prise en compte des parcours des femmes rencontrées et du contexte du nouveau management public structurant l'action publique, enrichissent la compréhension du travail social féministe mis en œuvre dans les structures d'accueil et d'hébergement des femmes victimes de violences conjugales et de leurs enfants. Cette recherche sociologique éclaire alors des engagements féministes professionnels trop peu connus, face au paradoxe d'un intérêt politique fort pour lutter contre des violences masculines toujours persistantes.
Keywords: 2000 à aujourd'hui; 2010-2019; cours; cycles supérieurs; discipline; fem7000; histoire et politique; périodes historiques; sciences humaines; thématiques; travail social; violences; violences conjugales

“Me Too”: Epistemic Injustice and the Struggle for Recognition - Jackson, Debra L. (Feminist Philosophy Quarterly, 2018)
Congdon (2017), Giladi (2018), and McConkey (2004) challenge feminist epistemologists and recognition theorists to come together to analyze epistemic injustice. I take up this challenge by highlighting the failure of recognition in cases of testimonial and hermeneutical injustice experienced by victims of sexual harassment and sexual assault. I offer the #MeToo movement as a case study to demonstrate how the process of mutual recognition makes visible and helps overcome the epistemic injustice suffered by victims of sexual harassment and sexual assault. I argue that in declaring “me too,” the epistemic subject emerges in the context of a polyphonic symphony of victims claiming their status as agents who are able to make sense of their own social experiences and able to convey their knowledge to others.
Keywords: #metoo; 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; harcèlement sexuel; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; philosophie féministe; périodes historiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éthique

The Institution of Gender-Based Asylum and Epistemic Injustice: A Structural Limit - Sertler, Ezgi (Feminist Philosophy Quarterly, 2018)
One of the recent attempts to explore epistemic dimensions of forced displacement focuses on the institution of gender-based asylum and hopes to detect forms of epistemic injustice within assessments of gender related asylum applications. Following this attempt, I aim in this paper to demonstrate how the institution of gender-based asylum is structured to produce epistemic injustice at least in the forms of testimonial injustice and contributory injustice. This structural limit becomes visible when we realize how the institution of asylum is formed to provide legitimacy to the institutional comfort the respective migration courts and boards enjoy. This institutional comfort afforded to migration boards and courts by the existing asylum regimes in the current order of nation-states leads to a systemic prioritization of state actors’ epistemic resources rather than that of applicants, which, in turn, results in epistemic injustice and impacts the determination of applicants’ refugee status.
Keywords: approches et analyses; capitalisme; confort institutionnel; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; institutions; migration; philosophie; politiques migratoires; racisme; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Violences conjugales : du combat féministe à la cause publique - Delage, Pauline (Domaine Genre, 2017)
« Si la violence conjugale est aujourd'hui reconnue comme une question de société légitime, il n'en a pas toujours été ainsi. C'est grâce aux mobilisations féministes des années 1970, qui définissent alors la violence dans le couple comme une violence faite aux femmes - produit des rapports de domination entre les hommes et les femmes -, que ce phénomène est sorti de la dénégation sociale dans laquelle il était tenu. Comment une cause féministe devient-elle un problème public dont s'emparent les associations, les institutions internationales et l'État ? À travers la question des violences conjugales et en comparant des cas français et américain, à Paris et à Los Angeles, Pauline Delage analyse avec acuité quelles sont, de part et d'autre de l'Atlantique, les formes légitimes de l'intervention publique dans le domaine de l'intime et des inégalités sexuées. » -- Résumé de l'éditeur.
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cours; cycles supérieurs; europe; fem7000; france; histoire et politique; mobilisation; périodes historiques; rapports de domination; rapports sociaux de sexe; ressource en ligne; régions géographiques; thématiques; transféminisme; violences; violences conjugales; états-unis

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge handbooks in philosophy, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice--one of the most important and ground-breaking subjects to have emerged in philosophy in recent years--refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

Credibility Excess and the Social Imaginary in Cases of Sexual Assault - Yap, Audrey S (Feminist Philosophy Quarterly, 2017)
This paper will connect literature on epistemic injustice with literature on victims and perpetrators, to argue that in addition to considering the credibility deficit suffered by many victims, we should also consider the credibility excess accorded to many perpetrators. Epistemic injustice, as discussed by Miranda Fricker, considers ways in which someone might be wronged in their capacity as a knower. Testimonial injustice occurs when there is a credibility deficit as a result of identity-prejudicial stereotypes. However, criticisms of Fricker have pointed out that credibility is part of a more complex system that includes both deficits and excesses. I will use these points to argue that we should look closer at sources of credibility excess in cases of sexual assault. This means that in addition to considering sources of victim blaming by looking at ways in which “ideal” victims are constructed, we also need to consider ways in which “ideal” perpetrators are constructed.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; inégalités; philosophie; philosophie féministe; privilèges; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éxcès de crédibilité

Epistemic Exploitation - Berenstain, Nora (Ergo, an Open Access Journal of Philosophy, 2016)
Epistemic exploitation occurs when privileged persons compel marginalized persons to educate them about the nature of their oppression. I argue that epistemic exploitation is marked by unrecognized, uncompensated, emotionally taxing, coerced epistemic labor. The coercive and exploitative aspects of the phenomenon are exemplified by the unpaid nature of the educational labor and its associated opportunity costs, the double bind that marginalized persons must navigate when faced with the demand to educate, and the need for additional labor created by the default skepticism of the privileged. I explore the connections between epistemic exploitation and the two varieties of epistemic injustice that Fricker (2007) identifies, testimonial and hermeneutical injustice. I situate epistemic exploitation within Dotson’s (2012; 2014) framework of epistemic oppression, and I address the role that epistemic exploitation plays in maintaining active ignorance and upholding dominant epistemic frameworks.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; exploitation épistémique; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; oppression épistémique; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; travail; violences; éthique

Typecasts, Tokens, and Spokespersons: A Case for Credibility Excess as Testimonial Injustice - Davis, Emmalon (Hypatia, 2016)
Miranda Fricker maintains that testimonial injustice is a matter of credibility deficit, not excess. In this article, I argue that this restricted characterízation of testimonial injustice is too narrow. I introduce a type of identity-prejudicial credibility excess that harms its targets qua knowers and transmitters of knowledge. I show how positive stereotyping and prejudicially inflated credibility assessments contribute to the continued epistemic oppression of marginalized knowers. In particular, I examine harms such as typecasting, compulsory representation, and epistemic exploitation and consider what hearers are obligated to do in response to these injustices. I argue that because epistemic harms to rnarginatized knowers also arise from prejudicially inflated assessments of their credibility, the virtue of testimonial justice must be revised to remedy them.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droits des personnes; excès de crédibilité; fem9000; fricker; injustices testimoniales; inégalités; justice sociale; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Normal life: Administrative violence, critical trans politics, and the limits of law - Spade, Dean (Book collections on Project MUSE, 2015)
Attendez—qu'est-ce qui ne va pas avec les droits ? On suppose généralement que les personnes transgenres et non conformes au genre devraient suivre les stratégies de droits civils et «d'égalité» des organisations de défense des droits des lesbiennes et des homosexuels en faisant campagne pour des réformes juridiques qui garantiraient ostensiblement la non-discrimination et une protection égale devant la loi. Cette approche suppose que la meilleure façon de lutter contre la pauvreté et la criminalisation qui affligent les populations trans est d'obtenir une reconnaissance légale et une inclusion dans les institutions de l'État. Mais cette stratégie est-elle efficace ? Dans la vie normaleDean Spade présente des critiques révélatrices du cadre d'égalité juridique pour le changement social et pointe des exemples d'activisme trans populaire transformateur qui soulève des demandes qui vont au-delà des réformes traditionnelles des droits civiques. Spade explose les hypothèses sur ce que les droits légaux peuvent faire pour les populations marginalisées et décrit les processus et les formations de résistance transformatrice qui s'attaquent aux causes profondes du mal et de la violence. Dans la nouvelle postface de cette édition révisée et augmentée, Spade note l'intégration rapide de la politique trans et constate que ses prédictions selon lesquelles l'obtention d'une reconnaissance légale ne profitera pas aux populations trans se concrétisent. Spade examine les efforts récents de l'administration Obama et des défenseurs de l'égalité des trans pour "pinkwash" la violence d'État en articulant les systèmes militaires et pénitentiaires américains comme des sites pour les réformes d'inclusion des trans. Dans le contexte de la récente visibilité accrue des personnes trans et de la politique trans, Spade continue de plaider pour le démantèlement des systèmes de violence d'État qui raccourcissent la vie des personnes trans. Aujourd'hui plus que jamais, Normal Life est un appel urgent à la justice et à la libération trans, et aux transformations radicales que cela nécessitera.
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; droit; fem9000; identités LGBTQIA2+; militance; personnes trans*; ressource en ligne; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; violences; états-unis

Epistemic Justice as a Virtue of Social Institutions - Anderson, Elizabeth (Social Epistemology, 2012)
In Epistemic injustice, Miranda Fricker makes a tremendous contribution to theorizing the intersection of social epistemology with theories of justice. Theories of justice often take as their object of assessment either interpersonal transactions (specific exchanges between persons) or particular institutions. They may also take a more comprehensive perspective in assessing systems of institutions. This systemic perspective may enable control of the cumulative effects of millions of individual transactions that cannot be controlled at the individual or institutional levels. This is true not only with respect to the overall distribution of such goods as income and wealth, but also with respect to the goods of testimonial and hermeneutical justice. Cognitive biases that may be difficult for even epistemically virtuous individuals to correct on their own may be more susceptible to correction if we focus on the principles that should govern our systems of testimonial gathering and assessment. Hence, while Fricker’s focus on individual epistemic virtue is important, we also need to consider what epistemic justice as a virtue of social systems would require. My paper will indicate some directions forward on this front, focusing on the need for integration of diverse institutions and persons engaged in inquiry.
Keywords: approches et analyses; biais cognitifs; capitalisme; cours; cycles supérieurs; discipline; droits des personnes; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; justice épistémique; philosophie; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Les femmes de droite - Dworkin, Andrea (Les éditions du remue-ménage, 2012)
Militante féministe, Andrea Dworkin a voulu comprendre pourquoi des femmes rejettent le féminisme et n’hésitent pas à se montrer racistes et homophobes. Comment expliquer cet apparent paradoxe? Dans un contexte où les femmes sont subordonnées aux hommes, les femmes de droite concluent ce qui leur paraît le marché le plus avantageux: en échange de leur conformité aux rôles traditionnels, la droite leur promet la sécurité, le respect, l’amour. Elles font donc le pari qu’il est préférable de prendre le parti du patriarcat plutôt que de combattre ce système dont la violence est trop souvent meurtrière. Mais la droite et l’antiféminisme se fondent sur le mépris des femmes et encouragent l’exploitation de leur sexualité: «ce que font les femmes de droite pour survivre au système de classes de sexe ne signifie pas qu’elles y survivront: si elles sont tuées, ce sera probablement aux mains de leur mari.» Une réflexion brutale et sans concession, qui appelle à la révolte féministe.
Keywords: amériques; antiféminisme; approches et analyses; corps; cours; cycles supérieurs; fem1000; fem7000; lit2815; lit3220; lit3495; militance; pornographie; premier cycle; régions géographiques; sexualité; thématiques; violences; violences sexistes et sexuelles; états-unis

Tracking Epistemic Violence, Tracking Practices of Silencing - Dotson, Kristie (Hypatia, 2011)
oo often, identifying practices of silencing is a seemingly impossible exercise. Here I claim that attempting to give a conceptual reading of the epistemic violence present when silencing occurs can help distinguish the different ways members of oppressed groups are silenced with respect to testimony. I offer an account of epistemic violence as the failure, owing to pernicious ignorance, of hearers to meet the vulnerabilities of speakers in linguistic exchanges. Ultimately, I illustrate that by focusing on the ways in which hearers fail to meet speaker dependency in a linguistic exchange, efforts can be made to demarcate the different types of silencing people face when attempting to testify from oppressed positions in society.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices épistémiques; inégalités; justice; philosophie; sciences humaines; silenciation; systèmes d'oppressions; thématiques; témoignage; violences; vulnérabilité; éthique